2014
DOI: 10.1172/jci71951
|View full text |Cite|
|
Sign up to set email alerts
|

CXCL11-dependent induction of FOXP3-negative regulatory T cells suppresses autoimmune encephalomyelitis

Abstract: A single G protein-coupled receptor (GPCR) can activate multiple signaling cascades based on the binding of different ligands. The biological relevance of this feature in immune regulation has not been evaluated. The chemokine-binding GPCR CXCR3 is preferentially expressed on CD4+ T cells, and canonically binds 3 structurally related chemokines: CXCL9, CXCL10, and CXCL11. Here we have shown that CXCL10/CXCR3 interactions drive effector Th1 polarization via STAT1, STAT4, and STAT5 phosphorylation, while CXCL11/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(90 citation statements)
references
References 69 publications
3
82
0
1
Order By: Relevance
“…Second, chemokines expressed in specific lymphoid compartments may influence more globally the positioning of T cells in particular microenvironments, to bring these cells in contact with the appropriate APCs or accessory cells important for their differentiation [9, 37, 38]. Chemokine receptors are 7-transmembrane GPCRs, and thus may transmit diverse signaling cascades upon binding to different ligands to determine T cell fate [10]. Specifically, CXCL10/CXCR3 interactions drive effector Th1 polarization via STAT1, STAT4, and STAT5 phosphorylation, while CXCL11/CXCR3 binding induces an immune-tolerizing state characterized by IL-10 hi (Tr1) and IL-4 hi (Th2) cells, mediated via p70 kinase/mTOR in STAT3- and STAT6-dependent pathways [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, chemokines expressed in specific lymphoid compartments may influence more globally the positioning of T cells in particular microenvironments, to bring these cells in contact with the appropriate APCs or accessory cells important for their differentiation [9, 37, 38]. Chemokine receptors are 7-transmembrane GPCRs, and thus may transmit diverse signaling cascades upon binding to different ligands to determine T cell fate [10]. Specifically, CXCL10/CXCR3 interactions drive effector Th1 polarization via STAT1, STAT4, and STAT5 phosphorylation, while CXCL11/CXCR3 binding induces an immune-tolerizing state characterized by IL-10 hi (Tr1) and IL-4 hi (Th2) cells, mediated via p70 kinase/mTOR in STAT3- and STAT6-dependent pathways [10].…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine receptors are 7-transmembrane GPCRs, and thus may transmit diverse signaling cascades upon binding to different ligands to determine T cell fate [10]. Specifically, CXCL10/CXCR3 interactions drive effector Th1 polarization via STAT1, STAT4, and STAT5 phosphorylation, while CXCL11/CXCR3 binding induces an immune-tolerizing state characterized by IL-10 hi (Tr1) and IL-4 hi (Th2) cells, mediated via p70 kinase/mTOR in STAT3- and STAT6-dependent pathways [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the distinct functional outcomes elicited by CXCL10 and CXCL11 downstream of CXCR3 can drive opposing cellular and physiologic consequences. For instance, CXCL11 signaling promotes Th1 cell polarization into an immunotolerant T cell subset, resulting in an anti-inflammatory phenotype in a mouse model of multiple sclerosis, whereas CXCL10 promotes pro-inflammatory effects [105]. …”
Section: Beyond Site 15mentioning
confidence: 99%
“…The data were aligned with other studies focused on the phenotype or functional analysis of Tregs, they had revealed Treg which isolated from patients with autoimmune disorder reduced regulatory function comparing with healthy individual Tregs [17]. Treg devoted to aiding immune tolerance, hence their expansion is necessary for the resolution of inflammation and in preventing tissue damage or autoimmunity [18]. Tregs are usually characterized by the expression of FOXP3, which is the main transcription factor and also a master regulator of the immune suppressive activity of Treg [19].…”
Section: Discussionmentioning
confidence: 80%